PENINGKATAN EFEKTIVITAS PELATIHAN TABLETOP PERSONEL PERTOLONGAN KECELAKAAN PESAWAT DAN PEMADAM KEBAKARAN (PKP-PK) DI BANDAR UDARA INTERNASIONAL YOGYAKARTA - Alfareza Chandra Prasetya; Wahyudono; Kardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Tabletop training is a crucial method for PKP-PK personnel to enhance preparedness in dealing with airport emergency situations. However, tabletop training at Yogyakarta International Airport is still conducted manually, which is considered inefficient, tedious, and lacking in visualization. This study aims to analyze the effectiveness of tabletop training before and after the implementation of digital media, as well as to evaluate the role of digitalization in improving training efficiency. This research employs a qualitative approach, with data collected through field observations, interviews, and document studies related to tabletop training activities conducted by PKP-PK personnel. The findings indicate that manual training methods have several limitations, such as lack of visualization, low participant engagement, and poorly documented evaluations. Based on document analysis and field findings, a web-based digital training system was developed as a solution to improve material comprehension, active participation, and evaluation effectiveness. This innovation is expected to enhance the preparedness of PKP-PK personnel in responding to emergencies in a more efficient and structured manner.